Optimization of fermentation process conditions of polyphenol⁃enriched highland barley monascus rice and its antioxidant activity research - WU Haiyu; HE Bingtao; YANG Jing; FAN Meixiang; DANG Bin (Shipin yu jixie)
ObjectiveThis study aimed to provide the basis for the development of highland barley monascus food.MethodsUsing highland barley as raw material, the suitable monascus strains with rich polyphenols were screened out, and the fermentation process of highland barley and monascus rice was optimized. The composition, content and antioxidant activity of polyphenols in highland barley after fermentation with monascus were determined by LC-MS/MS.ResultsBased on the contents of polyphenols and flavonoids, the suitable monascus species ACCC30352 for the enrichment of polyphenols in highland barley monascus rice fermentation was screened. The optimal fermentation process for polyphenol enrichment of highland barley was determined by orthogonal experiment as follows: 10% inoculation amount, pH 5 of soaking water, fermentation at 25 ℃ for 18 d. The contents of total polyphenols and flavonoids were 124.03% and 196.58% higher than those of unfermented highland barley, respectively. Compared with unfermented highland barley, the increase of phenolic substances in highland barley was mainly free phenolic acid and free flavonol, which were 2.28 times and 1.12 times, respectively. Among them, benzoic acid, syringic acid, vanillic acid, protocatechuic acid, p-hydroxybenzoic acid and ferulic acid are the main characteristic phenolic acids in highland barley monascus rice, and rutin and catechin are the main characteristic flavonoids in highland barley monascus rice. The DPPH, ABTS free radical scavenging capacity and FRAP reducing capacity of the highland barley were 1.39 times, 12.48 times and 2.65 times of the unfermented highland barley, respectively. Endoglucanase, β-glucosidase and acid protease secreted by monascus play an important role in increasing the content and composition of phenolic substances in highland barley.ConclusionMonascus fermentation can significantly increase the polyphenol content and antioxidant activity in highland barley.